Design of a remote control system for maintaining and repairing tasks in NPP - Hocheol Shin; You-rak Choi; Chang-hoi Kim (2017 14th International Conference on Ubiquitous Robots and Ambient Intelligence (URAI), 2017)
This paper describes the design of a remote control system for maintaining and repairing tasks in a nuclear power plant (NPP). As the remote target tasks, we set up a remote manipulation of the manual operation mechanism of the nuclear fuel changer of the heavy water NPP and remote pipe cutting/welding, which may be necessary in the case of an emergency or dismantling of the NPP. The system to be developed is composed of a master device, a slave robot, and a mobile platform, as well as a telescopic mast that moves the slave robot to the desired position. To effectively perform remote tasks, we designed the architecture of an integrating program. The integrating program has a system components control module, a virtual guide implementing module, and egocentric remote control algorithms. We also designed psychophysics experiment for evaluating the individual technologies and integrated systems.